Incidence and predictors of glaucoma following surgery for congenital cataract in the first year of life in Victoria, Australia. (12th March 2013) - Ruddle, Jonathan B; Staffieri, Sandra E; Crowston, Jonathan G; Sherwin, Justin C; Mackey, David A
Abstract Aim To determine the incidence and predictors of glaucoma following surgery for congenital and infantile cataract in an Australian population. Design Retrospective cohort study. Participants Infants (<12 months) having had lens extraction between January 1992 and May 2006, from two tertiary referral centres. Methods Children with uveitis, anterior segment dysgenesis, aniridia, retinopathy of prematurity, and lens subluxation were excluded. Potential predictors of incident glaucoma were examined using Cox proportional hazards regression with adjustment for clustering between eyes. Main Outcome Measures Incidence and predictors of secondary glaucoma. Results One hundred and forty‐seven eyes of 101 patients (46 bilateral cataract; 55 unilateral cataract) were included, with median follow‐up of 9.9 years (range 1.2–18.9 years). Cumulative incidence of glaucoma was 32.0% for eyes (n = 47) and 30.7% (n = 31) for subjects. Incidence was higher in children with bilateral cataract (38.9 vs. 17.1%, p = 0.004). There were 3.9 cases of glaucoma per 100 person years of follow‐up, the incidence rate being highest for surgery performed in the first month of life. Children with glaucoma had longer median follow‐up (11.8 vs. 9.3 years, p = 0.005). Risk of glaucoma decreased with increasing months of age at operation: hazard ratio 0.79, 95% confidence interval 0.69–0.91, p = 0.001. Median visual acuity was worse in children with unilateral cataract (p < 0.001). Conclusions We identified an increased risk of glaucoma when cataract surgery was performed in younger infants, and in those with bilateral cataract. As glaucoma may develop over a decade following lens extraction, life‐long surveillance is needed to prevent glaucoma‐associated vision loss.